Ballistocardiography - Alzamora Castro, V. (1955)
There are many researchers who are regarded as precursors of modern ballistocardiography; have also been countless instruments with which for many years has tried to obtain records from the mechanical activity of the heart. The merit of a systematic study and a suitable instrument belongs to STARR, Philadelphia.